Characterization of nanopowders produced by electrical explosion of titanium wires; The 6th International Forum on Strategic Technology (IFOST-2012), Aug. 22-24, 2011 - Kwon Y.-S.; Ilyin A. P. Aleksandr Petrovich; Nazarenko O. B. Olga Bronislavovna; Root L. O. Lyudmila Olegovna; Tikhonov D. V. Dmitry Vladimirovich; Startseva E. V. Elena Viacheslavovna (2011, 2011)
Title screen